2004
DOI: 10.1021/jf048883r
|View full text |Cite
|
Sign up to set email alerts
|

Strecker-type Degradation Produced by the Lipid Oxidation Products 4,5-Epoxy-2-Alkenals

Abstract: Strecker degradation is one of the most important reactions leading to final aroma compounds in the Maillard reaction. In an attempt to clarify whether lipid oxidation products may be contributing to the Strecker degradation of amino acids, this study analyzes the reaction of 4,5-epoxy-2-alkenals with phenylalanine. In addition to N-substituted 2-(1-hydroxyalkyl)pyrroles and N-substituted pyrroles, which are major products of the reaction, the formation of both the Strecker aldehyde phenylacetaldehyde and 2-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 25 publications
10
108
1
Order By: Relevance
“…It seems that aldol condensation reactions of lipid oxidation aldehydes catalyzed by an amino acid are very important in the overall formation of aroma volatiles in such reaction mixtures. Thus, in addition to the degradation of amino acids induced by lipid oxidation products, which has been reported before by Hidalgo and co-workers, 3,4 amino-acid-induced degradations and further reactions of lipid oxidation products may be of considerable importance in thermally processed foods as well. In addition, most of the volatiles identified in this study have been reported as volatile constituents of thermally processed lipidrich food products, 21,29,32 indicating that the mechanisms explained play a role in the formation of food volatiles.…”
Section: ' Results and Discussionmentioning
confidence: 70%
“…It seems that aldol condensation reactions of lipid oxidation aldehydes catalyzed by an amino acid are very important in the overall formation of aroma volatiles in such reaction mixtures. Thus, in addition to the degradation of amino acids induced by lipid oxidation products, which has been reported before by Hidalgo and co-workers, 3,4 amino-acid-induced degradations and further reactions of lipid oxidation products may be of considerable importance in thermally processed foods as well. In addition, most of the volatiles identified in this study have been reported as volatile constituents of thermally processed lipidrich food products, 21,29,32 indicating that the mechanisms explained play a role in the formation of food volatiles.…”
Section: ' Results and Discussionmentioning
confidence: 70%
“…Fat content has a marked effect on the release of the volatile compounds from meat products (Chevance and Farmer, 1999;Carrapiso, 2007), and also has an outstanding influence, as their fatty acid profiles does, on the generation of volatile compounds (Mottram, 1998;Elmore et al, 2002;Hidalgo and Zamora, 2004).…”
Section: Detection Of Differences Caused By the Feeding System Of Pigsmentioning
confidence: 99%
“…The formed compound, which was an intermediate in the reaction, was found to be phenylacetaldehyde. 16 Therefore the first step of the formation of PhIP is the Strecker degradation of phenylalanine to produce phenylacetaldehyde (Scheme 2), a step that does not need the presence of creati(ni)ne but is facilitated in 60 the presence of reactive carbonyl compounds derived from carbohydrates, 24,25 lipids, 26 amino acids, 27 or polyphenols 28 (see below). Once phenylacetaldehyde is formed, the reaction between phenylacetaldehyde and creati(ni)ne is produced to form in a first step 2-amino-5-(1-hydroxy-2-phenylethyl)-1-methyl-1H-imidazol-4(5H)-one and then, after dehydration, 2-amino-1-methyl-5-(2-phenylethylidene)-1H-imidazol-4(5H)-one.…”
Section: Foodsmentioning
confidence: 99%
“…35 However, in the course of lipid oxidation, many compounds analogous to α-dicarbonyl compounds are produced which are able to degrade amino acids similarly to the α-dicarbonyl compounds derived from carbohydrates. 15 The Strecker degradation of amino acids produced by secondary lipid oxidation products was firstly described in 2004 for the formation of phenylacetaldehyde by phenylalanine degradation in the presence of epoxyalkenals, 26 and later extended to other lipid-derived reactive carbonyls. [36][37][38] aldehyde formation by lipid oxidation products is believed to be produced analogously to amino acid degradation by α-dicarbonyl compounds.…”
Section: Other Degradative Pathways That Produce Strecker Aldehydes Amentioning
confidence: 99%